2021
DOI: 10.5812/ijcm.103653
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Celecoxib During Chemoradiation in Locally Advanced Head and Neck Carcinoma; A Phase 2 Randomized Placebo-Controlled Clinical Trial

Abstract: Background: Cyclo-oxygenase-2 (COX-2), an enzyme induced in pathological states, mediates the production of prostaglandins. Celecoxib as a selective COX-2 inhibitor may affect the outcome of treatments in several cancer types. Objectives: We conducted a randomized controlled double-blind clinical trial to evaluate the toxicity and efficacy of celecoxib administered concurrently with chemoradiation in locally advanced head and neck carcinomas. Methods: Patients with locally advanced head and neck carcinoma refe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Then we reviewed the full texts of the selected 102 studies and excluded 72 studies due to irrelevant data. Finally, 30 studies were included in this meta-analysis ( Figure 1 ) [ 29 , 30 , 31 , 32 , 33 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Then we reviewed the full texts of the selected 102 studies and excluded 72 studies due to irrelevant data. Finally, 30 studies were included in this meta-analysis ( Figure 1 ) [ 29 , 30 , 31 , 32 , 33 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 ].…”
Section: Resultsmentioning
confidence: 99%
“…As to second chemoprevention, celecoxib is an effective agent for the prevention of colorectal adenomas and familial adenomatous polyposis [ 14 , 77 ]. In terms of tertiary chemoprevention, also known as the clinical therapy phase, clinical studies reported that celecoxib improved the clinical efficacy of breast cancer, gastric cancer, rectal cancer, colorectal cancer, and head and neck cancer [ 29 , 30 , 46 , 50 , 56 ]. Celecoxib may exert its anticancer effects by reducing the production of COX-2-dependent PGE 2 and then inhibiting the COX-2/PGE 2 /EP 2 /p-AKT/p-ERK and PGE 2 /NF-kB pathways [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation